Effect of pelvic anatomical differences in 173 patients with low rectal cancer on the duration of laparoscopic intersphincteric resection - TIAN Shunhua; HU Heng; CHEN Baoxiang; HU Hang; JIANG Congqing (Yixue xinzhi zazhi)
Objective To exploring pelvic anatomical differences in patients with low rectal cancer and the effect on the duration of laparoscopic intersphincteric resection(ISR).Methods Clinical data from patients with low rectal cancer who underwent laparoscopic ISR from January 2017 to December 2022 in Zhongnan Hospital of Wuhan University were retrospectively collected. The 17 pelvic parameters such as pelvic inlet, pelvic outlet and pelvic depth etc. were measured from axial, sagittal and coronal positions based on CT/MRI. A comparative analysis of male and female pelvic anatomy was also performed to explore the factors affecting the duration of surgery through multiple linear regression.Results A total of 173 patients with low rectal cancer were included, of whom 107(61.8%) were male and 66(38.2%) were female, with a mean patient age of (58.06±9.91) years, BMI (22.65±3.15) kg/m2, operative time of (271.53±53.74) min. In the comparison of pelvic anatomical differences, the differences in 15 pelvic parameters such as pelvic inlet, pelvic outlet and pelvic depth were statistically significant between patients of different genders. Multiple linear regression analysis showed that the smaller intertuberous distance [95%CI(-25.554, -3.671), P=0.009] was an independent risk factor for longer operative time in male patients. The shallower sacral depth [95%CI(-166.166,-33.894), P=0.004] and larger angle α [95%CI(0.051, 5.499), P=0.046] were independent risk factors for prolonged operative time in female patients. Shallower sacral depth [95%CI(-95.657, -18.082), P=0.004], larger angle β [95%CI(0.258, 7.048), P=0.035], smaller angle δ [95%CI(-6.034, -0.627, P=0.016], smaller interberous distance [95%CI(-18.589, -2.511), P=0.010] and larger mesorectal fat area (P=0.043) were independent risk factors for prolonged operative time in patients with low rectal cancer.Conclusion The pelvic anatomy of patients with low rectal cancer differs significantly between genders, and anatomical factors affecting the duration of laparoscopic ISR vary among patients of different genders. Sacral depth, angle β, angle δ, intertuberous distance and mesorectal fat area are independent factors affecting operative time. Attention to these pelvic anatomical differences is important to guide clinical decision-making and improve surgical safety.